Advances in the mathematization process of Brazilian Academic Studies in Economics since the 1980s - Mauricio Martinelli Silva Luperi (Cogent Economics & Finance, 2014)
Looking at Brazilian economic discourse, in this article, we look at how mathematization of economics has advanced in the country in the last three decades. For this, we have classified into several categories all articles published in three major Brazilian economic journals (Revista Brasileira de Economia, Estudos Econômicos, and Revista de Economia Política) and the publications of ANPEC meetings from 1981 to 2010, according to the type of argument used. A total of 5,733 articles were analyzed. We attempt to see how mathematization of economic discourse developed, and found that there was an increased use of a formalized language from the mid-1990s onwards. Finally, to confirm our findings, we focus on the process of mathematization through the observation of a quantitative variable: equations per article.
Keywords: 330; mathematization; process; discourse; Brazilian